ANALISIS MANAJEMEN KREDIT UNTUK MEMINIMALISIR KREDIT MACET PADA KSP KOPDIT SUBE HUTER - Nurtiana Lam; Wilhelmina Mitan; Konstantinus Pati Sanga (Program Studi Akuntansi Universitas Nusa Nipa, 2023)
This study aims to determine and analyze the application of credit management to minimize bad debts and credit management analysis related to NPL, CAR, LDR in KSP Kopdit Sube Huter. This study is included in the survey study, in which case the author went directly to the field to obtain data by conductinginterviews with credit department employees, managers and supervisory chairmen of KSP Kopdit Sube Huter. Based on the data, this study is included in a qualitative study with the aim of determining the extent of credit management applied to minimize bad debts and analysis of credit management related to NPL, CAR, and LDR in KSP Kopdit Sube Huter. This study uses a descriptive approach. The results of this study show that the implementation of credit management in KSP Kopdit Sube Huter has not been maximized. This is reinforced by evidence that the number of non-performing loans and the percentage of Non-Performing Loans (NPLs) from 2019 to 2021 tend to increase, but in terms of the standard ratio set by Bank Indonesia, Kopdit Sube Huter has reached the established standards, starting from the Capital Adequacy Ratio (CAR) and Loan Deposit Ratio (LDR).